Back to the present: Assimilation of late 19th century performance features among currently active violinists. Issue 5 (20th October 2021) - Ornoy, Eitan; Cohen, Shai
Abstract : Present-day inquiries into aspects of 19th century performance style mark the growing quest to revive practices of post-1800 music repertoire. This paper aims to trace whether there be found an impact of recordings made by 19th century violinists of coeval repertoire on current performers who've recorded the same works. Early, intermediate, and present-day recordings ( N = 81) of three late-romantic compositions were analyzed for the manner of execution of varied performance features. While similarities between early and current period players were traced to a certain extent, several early period distinctives are still rather absent from prevalent praxis. Results may shed light on performance style and interpretation of late C19 violin repertoire and on the influence of sonic documentation on 21st century players.